Er:YAG Lasers Versus Ultrasonic and Hand Instruments in Periodontal Therapy: Clinical Parameters, Intracrevicular Micro-organism and Leukocyte Counts - KADİR, TANJU (MARY ANN LIEBERT, INC, 2012)
Objective: The aim of this study was to compare the clinical parameters and crevicular cell population, particularly leukocyte counts, changes after initial periodontal therapy with different instruments by a chairside laboratory technique, in severe periodontitis patients. Background data: Although scaling and root planing (SRP) with hand curettes or ultrasonic scalers may alter the subgingival microbial composition and improve clinical parameters, it is known that this effect decreases as the pocket depth (PD) increases. Material and methods: Thirty systemically healthy subjects with severe chronic periodontitis were randomly assigned to three groups (n = 10), and were treated either with hand curettes, ultrasonic scalers, or Er:YAG laser alone. Clinical measurements were made before and 90 days after treatment. A total of four subgingival plaque samples were collected from pockets with a PD 4-6 and >= 7 mm and were analyzed with a phase-contrast microscopy for microorganism proportions and leukocyte counts at baseline and 7 and 90 days after treatment. Results: From day 0 to day 90, clinical parameters were significantly improved in all groups (p < 0.01), but there were no significant differences among groups. Laboratory assessments revealed significant differences in all groups between baseline, day 7, and day 90. However, considering changes from day 7 to day 90, hand curettes were the most successful for maintaining the levels of micro-organisms and leukocytes. Conclusions: Although Er:YAG lasers are promising in treating periodontitis, the results of this study favor finishing SRP with hand curettes. Moreover, as there is a similar tendency between micro-organism and leukocyte count changes, leukocyte counts may be used as chairside marker to evaluate the efficacy of SRP.
Keywords: ER-YAG LASER; INVOLVED ROOT SURFACES; UP SPLIT-MOUTH; IN-VITRO; SUBGINGIVAL CALCULUS; DEBRIDEMENT; ENDOTOXIN; EFFICACY; REMOVAL; DISEASE